Doses de molibdênio e nitrogênio em milho safrinha e efeito residual na cultura da soja em plantio direto - Caioni, Sheila [UNESP] (2015)
For the corn and soybean crops can express all their productive potential, they must be offered to them adequate conditions for normal development, in this sense, nitrogen is the nutrient that most limits the productivity of both. However, the fertilization with micronutrients is also needed for plant nutrition, including molybdenum, with a fundamental role together with the nitrogen in the synthesis of many essential metabolic reactions indispensable for plants. In this sense, the objective of this study was to evaluate the effect of different doses of Mo and N in the second crop corn, and its residual effect on soybean grown in the summer harvest. The experiment was conducted at the Experimental area of UNESP - Ilha Solteira Campus, located in Selviria county, Mato Grosso do Sul State. The first experiment with corn in experimental design was a randomized block design with split plot design with four replications, where were tested four nitrogen rates (0, 90, 135 and 180 kg ha -1 ) in the plot, having the urea as N source, and five doses of molybdenum (0, 10, 20, 30 and 40 g ha -1 ) in the sub-plots. The crop was sown on 05/25/2013, in spaced 0.90 m using the hybrid DKB 390 Pro2. The second experiment was conducted with soybean in the summer crop on the same plots of the previous experiment. The crop was sown on the date of 11/13/2013, in spacing of 0.45 m using the cultivar BRS Valiosa RR. Soybeans were conducted without molybdenum and nitrogen application to evaluate the residual effect of the treatments used in the corn experiment. We evaluated the productive and morphological components for corn (plant height, ear height, grain yield, thousand grain weight, number of grain rows, number of kernels per row, and diameter of the ear) and soybeans (plant height, number of pods per plant, number of branches per plant, thousand grain weight and grain yield). In both cultures assessed the nutritional ...